CERTAIN ISSUES OF THE APPLICATION OF IMPERATIVENORMS IN THE LAW ENFORCEMENT PRACTICEOF THE REPUBLIC OF ARMENIA - Haykyants, Armen (State and Law, 2025)
The reference to the institution of imperative norms established by the legislation of the Republic of Armenia in this scientific article is due to the inconsistent interpretation of these norms in the judicial practice of the RA. The precedent decision of the RA Court of Cassation in the administrative case VD/3882/05/22 directly contradicts the legal regulations of Section 12 of the RA Civil Code and may lead to undesirable consequences in both judicial and notarial practice. Notaries in the RA who refuse to accept powers of attorney issued abroad with a validity period exceeding three years and to perform legally significant actions based on them may face judicial appeals. In turn, judicial authorities will be guided by the precedent decision of the RA Court of Cassation in case VD/3882/05/22, issuing contradictory rulings. There is an urgent need to review the controversial precedent decision of the RA Court of Cassation and to contribute to the development of law as well as the unification of judicial, notarial, and overall legal practice. Legal science plays a significant role in addressing this issue, and from this perspective, the article attempts to scientifically substantiate the vulnerability of the court’s decision and propose solutions to the existing situation.
Keywords: globalization; international cooperation; conflict rule; super-imperative rule; cassation court; precedent decision; extraterritorial; civil code